2008
DOI: 10.4049/jimmunol.180.10.6484
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of TCR-β Locus and HLA to the Shape of the Mature Human Vβ Repertoire

Abstract: T cells that survive thymic selection express a diverse array of unique heterodimeric αβ TCRs that mediate peptide-MHC Ag recognition. The proportion of the total T cell repertoire that expresses a particular Vβ protein may be determined by a variety of factors: 1) germline preference for use of particular Vβ genes; 2) allelic effects on the expression of different Vβ genes; and 3) HLA effects on the expression of different Vβ genes (acting via thymic selection and/or peripheral mechanisms). In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…Notably, the relative frequency of gene segment usage established during recombination is very similar to that found after thymic selection [46]. Moreover, biased V β usage by human CD4 + and CD8 + T cells in neonatal and adult donors is highly correlated between unrelated individuals, and the correlation in biased V β expression patterns between CD4 + and CD8 + T cells can be dominantly determined by germline TCR β locus factors rather than thymic selection [48]. Other observed recombinatorial biases include the extent of the removal of nucleotides from the germline gene segments and additions of specific 'random' nucleotides.…”
Section: Recombinatorial Biasesmentioning
confidence: 62%
See 2 more Smart Citations
“…Notably, the relative frequency of gene segment usage established during recombination is very similar to that found after thymic selection [46]. Moreover, biased V β usage by human CD4 + and CD8 + T cells in neonatal and adult donors is highly correlated between unrelated individuals, and the correlation in biased V β expression patterns between CD4 + and CD8 + T cells can be dominantly determined by germline TCR β locus factors rather than thymic selection [48]. Other observed recombinatorial biases include the extent of the removal of nucleotides from the germline gene segments and additions of specific 'random' nucleotides.…”
Section: Recombinatorial Biasesmentioning
confidence: 62%
“…All these evidence strongly suggests that β-selection and TCRαβ heterodimer formation do not favor any particular V β -J β combinations. In addition, biased V β usage by human CD4 + and CD8 + T cells in neonatal and adult donors is highly correlated between unrelated individuals, and the correlation in biased V β expression patterns between CD4 + and CD8 + T cells can be explained by germline TCR β locus factors, but not TCR β allelic or HLA effects [63].…”
Section: The Role Of Thymic Selection In Tcr Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, public TCR reported in the literature may have a probabilistic advantage to expand after antigenic stimulation simply because they belong to highly represented V-J rearrangement combinations. In another set of experiments, T-cell repertoires were compared in either genetically related or unrelated adult donors by flow cytometry [30]. These investigators confirmed a limited role of HLA haplotype and of the environment in shaping the T-cell repertoire.…”
Section: Discussionmentioning
confidence: 83%
“…Regarding clustering of the hTRBV genes, three major groups were observed (Fig. 4A, vertical dendrogram): the distribution of J elements within BV15,18,25,10,29,24,30 These are not the final page numbers (C6, C12, PBMC3, PBMC5, C10, C13, C14, C4, C11, C7 and C8), the other half being closer to the mean. The second group showed perturbation in the distribution of J elements within BV16, 14 and 13 across all samples.…”
mentioning
confidence: 99%